Project Management Knowledge Areas and Skills for Managing Software and Cloud Projects: Overcoming Challenges - Hayajneh, Sofyan; Hamada, Mohammed; Aljawarneh, Shadi (Recent Advances in Computer Science and Communications, 2020)
Background: Cloud Computing has already started to revolutionize storing and accessing data. Although cloud computing is on its way to become a huge success, there are some challenges that arise while managing cloud services. This indeed reveals many new knowledge areas, skills and consequently new challenges that need to be overcome so that software project managers can cope and make use of the newly available cloud services. This research aims to identify the challenges faced by project managers in cloud computing and highlight the knowledge areas and skills required to meet these challenges. Methods: The findings of this paper are presented through three stages. First, the pre-survey questionnaire to validate skills and knowledge areas which will be selected and eventually adopted for the main survey. Second, interviews with experts in the field to discuss the challenges identified in the literature review and it will also be adopted with the pre-survey to build the main survey. Third, the main survey to identify the critical skills and knowledge areas that are required for managing cloud projects. Results: This study drew recommendations so that possible systems and tools can be developed and integrated to overcome some of these challenges that give it the importance of providing guidance for the managers in the field to improve the performance of project management successfully. Conclusion: This study leads to gain more understanding of the attributes of a competent cloud manager. It also determines knowledge areas and skills to help them effectively in overcoming the challenges faced in software and cloud projects.
Keywords: Competency